Analysing the Role of Social Visits on Migrants’ Social Capital: A Personal Network Approach - Viry, Gil (Social Inclusion, 2017)
There are concerns that migrants may be embedded in far-flung networks with support being less collective. The spatial dispersion of their relatives and friends would result in fragmented networks with lower solidarity and lower mutual trust than densely connected networks based on geographical proximity. This may be particularly true for migrants who rarely meet their relatives and friends face-to-face. Yet, it is unclear what role, if any, distant visits play in migrants’ social capital. This article examines these issues using representative data from Switzerland and a combination of network and sequence analysis. Results show that migrants have more spatially dispersed networks, which, in turn, are associated with higher number of emotional support ties compared to respondents with spatially close networks, yet they are characterised by low cohesion and low trust. Distant visits only partly moderate the influence of spatial dispersion on social capital. People who frequently visit or host their far-flung relatives and friends have more transitive networks and fewer supportive ties than those who see them less often, but they do not have higher trust in them. Overall, distant visits have relatively little impact on social capital, suggesting a network effect that goes beyond dyadic relationships.